2022
DOI: 10.1007/s00590-021-03198-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of platelet-rich plasma (PRP) analogues on healing and clinical outcomes following anterior cruciate ligament (ACL) reconstructive surgery: a systematic review

Abstract: Purpose To systematically review the effect of PRP on healing (vascularization, inflammation and ligamentization) and clinical outcomes (pain, knee function and stability) in patients undergoing ACL reconstruction and compare the preparation and application of PRP. Methods Independent systematic searches of online databases (Medline, Embase and Web of Science) were conducted following PRISMA guidelines (final search 10th July 2021). Studies were screened a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In the same year, by including a larger number of 17 RCTs, Lv et al [32] found moderate quality of evidence suggesting that PRP could provide short-term pain reduction. More recently, the meta-analysis of McRobb et al [39] on 13 RCTs concluded that PRP influences healing through early vascularisation, culminating in higher rates of ligamentisation, and the meta-analysis of Zhu et al [65] on 14 studies confirmed that PRP applied alongside ACLR could reduce postoperative pain and improve knee function in the short and medium terms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, by including a larger number of 17 RCTs, Lv et al [32] found moderate quality of evidence suggesting that PRP could provide short-term pain reduction. More recently, the meta-analysis of McRobb et al [39] on 13 RCTs concluded that PRP influences healing through early vascularisation, culminating in higher rates of ligamentisation, and the meta-analysis of Zhu et al [65] on 14 studies confirmed that PRP applied alongside ACLR could reduce postoperative pain and improve knee function in the short and medium terms.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponded to a simultaneous growth in the clinical application and in scientific publications, including those on ligament pathologies such as ACLR. With the aim of summarising the growing body of evidence, many systematic reviews have been published on this topic, and recently even meta-analyses in the attempt to quantify the potential benefits of this biological augmentation [14,32,39,65]. In 2021, the meta-analysis of de Andrade et al [14] focusing on nine studies concluded that PRP showed no improvement in objective outcomes like ligamentisation and less tunnel widening, while it showed small improvements in terms of Lysholm, VAS and knee laxity.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to our case which exhibited improvements in mean grey value following PRP treatment; however, our methodology utilised a control ROI around the PCL to reduce variability between scans and increase the interpretability of our findings (figure 4). However, evidence for PRP-augmented ACLR is less promising, where several systematic reviews have demonstrated limited improvements in long-term healing, functional outcomes or postoperative pain 10. Nevertheless, the use of PRP in ACL rupture may be a viable treatment in select patients such as those with partial tears or those who elect more conservative management options.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies have shown the positive effect of PRP in reducing pain and function improvement in lateral elbow tendinosis and patellar tendinopathy. McRobb et al 23 conducted a systematic review on the effect of PRP on healing and clinical outcomes after anterior cruciate ligament reconstructive surgery and showed no consensus on the impact of PRP on pain, knee stability, and resultant knee function. Currently, there is scarcity of evidence supporting the use of PRP for treating musculoskeletal soft tissue injuries.…”
Section: Introductionmentioning
confidence: 99%